Lake season ebook - Hunter, Denise (A Bluebell Inn Romance, 2019)
A young innkeeper falls in love with a reclusive novelist in a small North Carolina lake town. Past and present collide and old secrets beckon in this first installment of the Bluebell Inn Romance series. When her parents die in a tragic accident, Molly Bennett and her siblings pull together to fulfill their parents' dream of turning their historic Bluebell, North Carolina, home back into an inn. Staying in town would be temporary—three years at most—then they plan to sell the inn, and Molly can get back to chasing her own dreams. Adam Bradford (aka bestselling author Nathaniel Quinn) is a reclusive novelist with a bad case of writer's block. Desperate for inspiration as his deadline approaches, he travels to the setting of his next book, a North Carolina lake town. There, he meets his muse, a young innkeeper who fancies herself in love with his alter ego. Molly and Adam strike up an instant friendship. When Molly finds a long-lost letter in the walls of her inn, she and Adam embark on a mission to find the star-crossed lovers and bring them the closure they deserve. But Adam has secrets he isn't ready to share. Past and present collide as truths surface, and Molly and Adam will have to decide if love is worth trusting. Praise for Lake Season: "Nobody does summer romance better than Denise Hunter." — Julie Lessman , award-winning author Full-length romance novel Includes discussion questions for book clubs First book in the Bluebell Inn Romance series Book 1: Lake Season Book 2: Carolina Breeze Book 3: Autumn Skies